Determinants of Debt Policy with Profitability as a Moderating Variable - sulistiani, Ana; Agustina, Linda (Accounting Analysis Journal, 2019)
This study aims to examine the effect of sales growth, institutional ownership and company size on debt policy with profitability as a moderating variable. The research population was all of the property and real estate companies listed on the Indonesia Stock Exchange 2014-2017 as many as 61 companies. The sampling method used purposive sampling, so a sample of 34 companies was obtained with analysis units of 136. The data collection method used was the documentation method. The analysis technique of this research used multiple regression using the absolute difference test. The results show that sales growth and company size has a significant positive effect on debt policy. Institutional ownership has a significant negative effect on debt policy. Profitability significantly moderates the effect of sales growth and company size on debt policy. Profitability is not able to moderate institutional ownership on debt policy. The conclusion of this study is that all independent variables influence debt policy and profitability are able to moderate sales growth and company size but are not able to moderate institutional policy towards debt policy. Suggestions for further research can use other variables that are thought to influence debt policy.